Porous electrode material, preparation method thereof and electrolysis device
By using the grid-shaped high-entropy alloy NiFeCoCrAl as the porous electrode material, printing and electrochemical corrosion treatment through the selected laser melting process, the existing electrolytic catalysts have been solved, and efficient and stable electrolytic catalytic effect has been achieved.
Patent Information
- Application Number
- CN202311289186.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-09-27
AI Technical Summary
The existing electrolytic water catalysts have poor stability, low selectivity and high production costs in long-term water decomposition reactions, which affects the development of renewable energy.
The grid-shaped high-entropy alloy NiFeCoCrAl is used as the porous electrode material, and the active area and porosity of the electrode material are printed through the selected laser melting process and subjected to electrochemical corrosion.
The oxygen-producing activity and stability of the catalyst electrode are improved, the conductivity and catalytic effect in alkaline media are enhanced, the production cost is reduced, and the service life is extended.
Smart Images

Figure CN119710769A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrolytic hydrogen production, and in particular to a porous electrode material, a preparation method thereof and an electrolysis device. Background Art
[0002] Water electrolysis is an important technology for converting water into hydrogen and oxygen. It can use renewable energy such as solar energy and wind energy to produce hydrogen, thereby achieving sustainable energy development. Effective catalysts can improve the efficiency of water electrolysis and the rate of hydrogen production, reduce costs, and thus promote the development of renewable energy. Traditional water electrolysis catalysts, such as precious metals such as platinum and palladium, are expensive, which not only increases production costs, but also has an impact on the environment. In addition, water electrolysis catalysts can also be used to generate and store electricity, so they are also crucial to the development of energy conversion and storage technologies. Therefore, it is of great significance to develop low-cost and high-efficiency water electrolysis catalysts, which can promote the development of sustainable energy, promote the popularization of clean energy vehicles, promote the development of energy conversion and storage technologies, and achieve sustainable energy development.
[0003] Although researchers have developed a number of transition metal water electrolysis catalysts, there are still many problems, such as:
[0004] 1. The powder catalyst has poor stability. During the long-term water decomposition reaction, the catalyst is easily deactivated, falls off or wears out prematurely, resulting in a decrease in gas production efficiency. The catalyst needs to be replaced frequently, which reduces the economic benefits.
[0005] 2. Low selectivity: Some transition metal water electrolysis catalysts may produce unnecessary side reactions or products in the water splitting reaction, thereby reducing the efficiency of hydrogen production. In addition, the gas production rate of commercial nickel foam catalysts is slow, and a larger current density is required to achieve the same hydrogen production, thus requiring more energy costs.
[0006] Therefore, inventing a porous electrode material that can improve hydrogen production efficiency is a technical problem that needs to be solved urgently. Summary of the invention
[0007] In view of this, the present invention aims to solve the technical problem of low hydrogen production efficiency of existing catalyst electrodes.
[0008] A first aspect of the present invention provides a porous electrode material.
[0009] A second aspect of the present invention provides a method for preparing a porous electrode material.
[0010] A third aspect of the present invention provides an application of a porous electrode material.
[0011] A fourth aspect of the present invention provides a catalyst electrode.
[0012] A fifth aspect of the present invention provides an electrolysis device.
[0013] Specifically, the present invention is achieved through the following technical solutions:
[0014] The first aspect of the present invention provides a porous electrode material, comprising a grid-shaped high entropy alloy, wherein the composition of the high entropy alloy is Ni a Fe b Co c Cr d Al e , 30≤a≤37, 5≤b≤16.7, 5≤c≤16.7, 5≤d≤16.7, 5≤e≤16.7, a+b+c+d+e=100, the grid-like high entropy alloy surface has pores.
[0015] The porous electrode material provided by the present invention adopts five elements of Ni, Fe, Co, Cr and Al as raw materials of the catalyst electrode, so that the prepared porous electrode material has excellent electrolytic water oxygen production activity and stability in alkaline medium. In addition, the porous electrode of the present invention is a grid-like structure, and has pores on the grid-like surface, so that the active area of the electrode material is increased, more catalytic active sites are exposed, the porosity of the catalyst electrode is increased, and the catalytic effect is improved. It can be understood that the current electrode materials are usually electrochemically corroded by the entire bulk, so that the corrosion area is limited and the porosity is low, and the present invention first prepares the high entropy alloy into a grid shape, and then performs electrochemical corrosion treatment, so that the contact area with the corrosive liquid is greatly increased, the porosity is increased, and the catalytic effect is improved.
[0016] In the above technical solution, the pore diameter is greater than or equal to 150 μm and less than or equal to 1000 μm.
[0017] In this technical solution, the pore size is limited, which can improve the catalytic activity of the porous electrode material.
[0018] In the above technical solution, the mesh size of the mesh-shaped high entropy alloy is greater than or equal to 200 μm and less than or equal to 800 μm.
[0019] In this technical solution, the mesh size of the mesh-like high entropy alloy is limited. This can avoid the mesh size being too small, which increases the difficulty of preparing the mesh, and can also avoid the mesh size being too large, which reduces the porosity.
[0020] In the above technical solution, the grid-shaped high entropy alloy is printed by a selective laser melting process.
[0021] In this technical solution, a grid-shaped high entropy alloy can be printed by a selective laser melting process, for example, by a laser 3D metal printing device. The porous electrode material of the present invention effectively combines the selective laser melting process during the preparation process, thereby overcoming the conventional problem of low porosity caused by electrochemical corrosion of large blocks of alloys.
[0022] In the above technical solution, the pores are formed by electrochemical corrosion treatment.
[0023] In this technical solution, the pores are formed by electrochemical corrosion treatment, which can improve the pore-forming efficiency. Of course, it is not limited to electrochemical corrosion treatment, and it can also be etching treatment, etc.
[0024] In the above technical solution, the porous electrode material has a current density of 10 mA / cm in the electrocatalytic oxygen production test. 2 The overpotential is less than or equal to 285 mV, so that the porous electrode material of the present invention has good conductivity.
[0025] In the above technical solution, a=34.4, b=16.4, c=16.4, d=16.4, e=16.4.
[0026] In this technical solution, a=34.4, b=16.4, c=16.4, d=16.4, e=16.4, that is, the composition of the porous electrode material is Ni 34.4 Fe 16.4 Co 16.4 Cr 16.4 Al 16.4 By controlling the ratio of five elements, Ni, Fe, Co, Cr and Al, the stability, conductivity and catalytic effect of the porous electrode material in alkaline medium can be maximized.
[0027] In the above technical solution, the crystal structure of the grid-shaped high entropy alloy includes a face-centered cubic lattice and a body-centered cubic lattice.
[0028] In this technical solution, the high entropy alloy with a face-centered cubic lattice or a body-centered cubic lattice has a higher active area, thereby making the catalytic efficiency higher.
[0029] The second aspect of the present invention provides a method for preparing a porous electrode material, comprising the following steps: printing a high entropy alloy powder into a grid-shaped high entropy alloy of a first preset size by a selective laser melting process, wherein the composition of the high entropy alloy powder is Ni a Fe b Co c Cr d Al e, 30≤a≤37, 5≤b≤16.7, 5≤c≤16.7, 5≤d≤16.7, 5≤e≤16.7, a+b+c+d+e=100; the grid-shaped high entropy alloy is electrochemically corroded by a corrosive solution to obtain a porous electrode material.
[0030] The preparation method of the porous electrode material provided by the present invention is to first print a grid-shaped high entropy alloy from high entropy alloy powder by a selective laser melting process, and then electrochemically corrode the grid-shaped high entropy alloy by a corrosive liquid to obtain a grid-shaped porous electrode material. The grid-shaped porous electrode prepared by the present invention has pores on the grid-shaped surface, which increases the active area of the electrode material, exposes more catalytic active sites, and improves the porosity of the catalyst electrode, thereby improving the catalytic effect. It can be understood that the current electrode materials usually electrochemically corrode the entire bulk body, so that the corrosion area is limited and the porosity is low. The present invention first prepares the high entropy alloy into a grid shape, and then electrochemically corrodes it, so that the contact area with the corrosive liquid is greatly increased, the porosity is increased, and the catalytic effect is improved. In addition, the porous electrode material of the present invention effectively combines the selective laser melting process in the preparation process, so as to overcome the problem of low porosity caused by conventional electrochemical corrosion of large-block alloys.
[0031] In the above technical solution, the mesh size of the mesh-shaped high entropy alloy is greater than or equal to 200 μm and less than or equal to 800 μm.
[0032] In this technical solution, the mesh size of the mesh-like high entropy alloy is limited. This can avoid the mesh size being too small, which increases the difficulty of preparing the mesh, and can also avoid the mesh size being too large, which reduces the porosity.
[0033] In the above technical solution, the particle size of the high entropy alloy powder is greater than or equal to 15 μm and less than or equal to 45 μm.
[0034] In this technical solution, controlling the particle size of the high entropy alloy powder can accelerate the melting rate of the high entropy alloy powder and increase the printing rate.
[0035] In the above technical scheme, the step of printing a grid-shaped high-entropy alloy of a first preset size from high-entropy alloy powder through a selective laser melting process includes: drawing a grid-shaped structure model; importing the grid-shaped structure model into a laser 3D metal printing device, and printing it through the laser 3D metal printing device to obtain a grid-shaped high-entropy alloy of a first preset size.
[0036] In this technical solution, during the printing process of high entropy alloy powder, a grid structure model can be drawn first, the grid structure model can be imported into a laser 3D metal printing device, and then printed by the laser 3D metal printing device to obtain a grid-shaped high entropy alloy.
[0037] In the above technical solution, the length of the first preset dimension is greater than or equal to 40 mm and less than or equal to 60 mm; the width of the first preset dimension is greater than or equal to 10 mm and less than or equal to 30 mm; the height of the first preset dimension is greater than or equal to 10 mm and less than or equal to 30 mm.
[0038] In this technical solution, the length of the first preset size is greater than or equal to 40mm and less than or equal to 60mm; the width of the first preset size is greater than or equal to 10mm and less than or equal to 30mm; the height of the first preset size is greater than or equal to 10mm and less than or equal to 30mm. Further, the length, width and height of the first preset size are 50mm×20mm×20mm respectively, that is, during the printing process, the size of the printed grid-shaped high entropy alloy is 50mm×20mm×20mm. Controlling the size of the grid-shaped high entropy alloy can avoid the problem of too small size, resulting in slow printing efficiency, and on the other hand, it can also avoid the problem of too large size resulting in poor corrosion effect in the later stage.
[0039] In the above technical solution, after the step of printing a grid-shaped high entropy alloy of a first preset size from high entropy alloy powder through a selective laser melting process, it also includes: cutting the grid-shaped high entropy alloy of the first preset size to cut the grid-shaped high entropy alloy to a second preset size.
[0040] In this technical solution, after printing out the grid-shaped high entropy alloy, the grid-shaped high entropy alloy is sawed, which can increase the surface area of the grid-shaped high entropy alloy, and then during the electrochemical corrosion process, the contact area with the corrosive liquid can be increased to improve the pore formation rate.
[0041] In the above technical solution, the length of the second preset dimension is greater than or equal to 0.5 mm and less than or equal to 1 mm; the width of the second preset dimension is greater than or equal to 5 mm and less than or equal to 15 mm; the height of the second preset dimension is greater than or equal to 5 mm and less than or equal to 15 mm.
[0042] In this technical solution, the length of the second preset dimension is greater than or equal to 0.5 mm and less than or equal to 1 mm; the width of the second preset dimension is greater than or equal to 5 mm and less than or equal to 15 mm; the height of the second preset dimension is greater than or equal to 5 mm and less than or equal to 15 mm. Furthermore, the length, width and height of the second preset dimension are 0.8 mm×10 mm×10 mm, that is, the grid-shaped high entropy alloy is cut to a size of 0.8 mm×10 mm×10 mm, which can improve the later pore formation rate.
[0043] In the above technical solution, the etching solution includes an acid solution and ferrous sulfate.
[0044] In this technical solution, an acid solution and a mixed solution of ferrous sulfate are selected as the corrosive solution. Compared with a mixed solution of acid solution and chromium trioxide, it has a better corrosion effect and can make the porous electrode material have better alkali resistance stability and conductivity.
[0045] In the above technical solution, the acid solution includes hydrogen chloride.
[0046] In this technical solution, hydrogen chloride has a better pore-forming effect than other acid solutions.
[0047] In the above technical solution, the molar ratio of hydrogen chloride to ferrous sulfate is greater than or equal to 2:1 and less than or equal to 6:1.
[0048] In this technical solution, controlling the molar ratio of hydrogen chloride and ferrous sulfate can maximize the corrosion effect and improve the alkali resistance stability.
[0049] In the above technical solution, the concentration of hydrogen chloride is greater than or equal to 1 mol / L and less than or equal to 3 mol / L.
[0050] In this technical solution, controlling the concentration of hydrogen chloride can ensure the optimal pH value of the etching solution. Too high a concentration will result in an excessively high pH value of the etching solution, which is not conducive to pore formation and will affect the alkali resistance stability of the porous electrode material.
[0051] In the above technical solution, the concentration of ferrous sulfate is greater than or equal to 0.3 mol / L and less than or equal to 0.8 mol / L.
[0052] In this technical solution, the concentration of ferrous sulfate is greater than or equal to 0.3 mol / L and less than or equal to 0.8 mol / L, for example, 0.5 mol / L. This can ensure the pore-forming effect and avoid the problem of excessive ferrous sulfate resulting in insignificant improvement in the porosity, leading to material waste.
[0053] In the above technical solution, in the step of electrochemical corrosion treatment, the electrochemical corrosion treatment conditions include: direct current, power-on current greater than or equal to 1.5V and less than or equal to 2V, and power-on time greater than or equal to 1 minute and less than or equal to 5 minutes.
[0054] In this technical solution, electrochemical corrosion is performed by direct current. Furthermore, the current is greater than or equal to 1.5V and less than or equal to 2V, for example, the current is 1.8V, and the power-on time is greater than or equal to 1 minute and less than or equal to 5 minutes, for example, 3 minutes. By controlling the current and the power-on time, the pore-making effect can be improved while improving the utilization rate of energy and avoiding energy waste.
[0055] In the above technical solution, during the printing process, the printing environment of the laser 3D metal printing equipment is an argon environment.
[0056] In this technical solution, the printing environment of the laser 3D metal printing equipment is an argon environment, which can ensure a safe printing environment.
[0057] In the above technical solution, during the printing process, the diameter of the focused laser beam of the laser 3D metal printing device is greater than or equal to 70 μm and less than or equal to 120 μm.
[0058] In this technical solution, the diameter of the focused laser beam of the laser 3D metal printing device is greater than or equal to 70 μm and less than or equal to 120 μm. Furthermore, the diameter of the focused laser beam of the laser 3D metal printing device is 90 μm, which can ensure the printing speed and the accuracy of the pores, thereby improving the catalytic effect of the porous electrode material.
[0059] In the above technical solution, the laser power of the laser 3D metal printing equipment is greater than or equal to 300W and less than or equal to 500W.
[0060] In this technical solution, the laser power of the laser 3D metal printing device is greater than or equal to 300 W and less than or equal to 500 W. Furthermore, the laser power of the laser 3D metal printing device is 400 W. By controlling the laser power of the laser 3D metal printing device, the printing speed can be guaranteed, the accuracy of the pores can be ensured, and the catalytic effect of the porous electrode material can be improved.
[0061] In the above technical solution, during the printing process, the scanning speed of the laser of the laser 3D metal printing device is greater than or equal to 1000 mm / s and less than or equal to 1400 mm / s.
[0062] In this technical solution, during the printing process, the scanning speed of the laser of the laser 3D metal printing device is greater than or equal to 1000 mm / s and less than or equal to 1400 mm / s. Furthermore, the scanning speed of the laser of the laser 3D metal printing device is 1200 mm / s. By controlling the scanning speed of the laser of the laser 3D metal printing device, the printing rate can be guaranteed on the one hand, and the quality of the porous electrode material can be guaranteed on the other hand, so as to avoid the catalytic effect of the porous electrode material being affected by the printing speed being too fast.
[0063] In the above technical solution, the scanning pitch of the laser of the laser 3D metal printing device is greater than or equal to 0.05 mm and less than or equal to 0.15 mm.
[0064] In this technical solution, the scanning pitch of the laser of the laser 3D metal printing device is greater than or equal to 0.05 mm and less than or equal to 0.15 mm. Furthermore, the scanning pitch of the laser of the laser 3D metal printing device is equal to 0.09 mm. Controlling the scanning pitch of the laser of the laser 3D metal printing device can ensure the quality of the porous electrode material and improve the catalytic effect.
[0065] In the above technical solution, the thickness of each layer printed by the laser 3D metal printing device is greater than or equal to 20 μm and less than or equal to 40 μm.
[0066] In this technical solution, the thickness of each layer printed by the laser 3D metal printing device is greater than or equal to 20 μm and less than or equal to 40 μm. Furthermore, the thickness of each layer printed by the laser 3D metal printing device is 30 μm. Controlling the thickness of each layer printed by the laser 3D metal printing device can ensure the quality of the porous electrode material and improve the catalytic effect.
[0067] The technical solution of the third aspect of the present invention provides the use of the porous electrode material prepared by the porous electrode material of the technical solution of the first aspect of the present invention or the porous electrode material preparation method of any technical solution of the second aspect of the present invention in the electrolysis of water to produce hydrogen and / or oxygen.
[0068] The technical solution of the fourth aspect of the present invention provides a catalyst electrode, which is prepared by a porous electrode material according to any technical solution of the first aspect of the present invention, or a porous electrode material prepared by the preparation method of the porous electrode material according to any technical solution of the second aspect of the present invention.
[0069] The technical solution of the fifth aspect of the present invention provides an electrolysis device, comprising a catalyst electrode as described in the technical solution of the fourth aspect of the present invention.
[0070] Beneficial effect: The porous electrode material provided by the present invention has excellent water electrolysis oxygen production activity and stability in alkaline medium. -2 The required overpotential is 270mV to 280mV and can be applied at 500mA·cm -2 It can work continuously for 1000 hours under high temperature and its performance is better than that of nickel foam. BRIEF DESCRIPTION OF THE DRAWINGS
[0071] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0072] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or related technical descriptions are briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0073] Figure 1 A schematic flow chart of a method for preparing a porous electrode material provided in Example 1 of the present invention;
[0074] Figure 2 A schematic diagram of a process for preparing a porous electrode material provided in Example 2 of the present invention;
[0075] Figure 3 A schematic flow chart of a method for preparing a porous electrode material provided in Example 3 of the present invention;
[0076] Figure 4 A schematic flow chart of a method for preparing a porous electrode material provided in Example 4 of the present invention;
[0077] Figure 5 A schematic flow chart of a method for preparing a porous electrode material provided in Comparative Example 1 of the present invention;
[0078] Figure 6 A schematic flow chart of a method for preparing a porous electrode material provided in Comparative Example 2 of the present invention;
[0079] Figure 7 A linear voltammetric scanning curve diagram of hydrogen evolution and oxygen evolution in an electrochemical test of the porous electrode material provided in Example 1 of the present invention;
[0080] Figure 8 A linear voltammetric scanning curve diagram of hydrogen evolution and oxygen evolution in an electrochemical test of a porous electrode material provided in Example 2 of the present invention;
[0081] Fig. 9 A linear voltammetric scanning curve diagram of hydrogen evolution and oxygen evolution in an electrochemical test of a porous electrode material provided in Example 3 of the present invention;
[0082] Fig.10 A scanning electron microscope image of a porous electrode material prepared by the method for preparing a porous electrode material provided in Example 1 of the present invention;
[0083] Fig.11 A scanning electron microscope image of a porous electrode material prepared by the method for preparing a porous electrode material provided in Example 2 of the present invention;
[0084] Fig.12 A scanning electron microscope image of a porous electrode material prepared by the method for preparing a porous electrode material provided in Example 3 of the present invention;
[0085] Fig.13 A schematic block diagram of an electrolysis device provided in an embodiment of the present invention.
[0086] in, Fig.13 The corresponding relationship between the component names and numbers in is as follows:
[0087] 1. Electrolysis device, 12. Catalyst electrode. DETAILED DESCRIPTION
[0088] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0089] The embodiment of the first aspect of the present invention provides a porous electrode material, comprising a grid-shaped high entropy alloy, wherein the composition of the high entropy alloy is Ni a Fe b Co c Cr d Al e , 30≤a≤37, 5≤b≤16.7, 5≤c≤16.7, 5≤d≤16.7, 5≤e≤16.7, a+b+c+d+e=100, the grid-like high entropy alloy surface has pores.
[0090] The porous electrode material provided by the present invention adopts five elements of Ni, Fe, Co, Cr and Al as raw materials of the catalyst electrode, so that the prepared porous electrode material has excellent electrolytic water oxygen production activity and stability in alkaline medium. In addition, the porous electrode of the present invention is a grid-like structure, and has pores on the grid-like surface, so that the active area of the electrode material is increased, more catalytic active sites are exposed, the porosity of the catalyst electrode is increased, and the catalytic effect is improved. It can be understood that the current electrode materials are usually electrochemically corroded by the entire bulk, so that the corrosion area is limited and the porosity is low, and the present invention first prepares the high entropy alloy into a grid shape, and then performs electrochemical corrosion treatment, so that the contact area with the corrosive liquid is greatly increased, the porosity is increased, and the catalytic effect is improved.
[0091] In the above embodiment, the pore diameter is greater than or equal to 150 μm and less than or equal to 1000 μm.
[0092] In this embodiment, the pore size is limited, which can improve the catalytic activity of the porous electrode material.
[0093] In the above embodiment, the mesh size of the mesh-shaped high entropy alloy is greater than or equal to 200 μm and less than or equal to 800 μm.
[0094] In this embodiment, the mesh size of the mesh-like high entropy alloy is limited, which can avoid the mesh size being too small, increasing the difficulty of preparing the mesh, and can also avoid the mesh size being too large, reducing the porosity.
[0095] In the above embodiment, the grid-shaped high entropy alloy is printed by a selective laser melting process.
[0096] In this embodiment, a grid-shaped high entropy alloy can be printed by a selective laser melting process, for example, by a laser 3D metal printing device. The porous electrode material of the present invention effectively combines the selective laser melting process during the preparation process, thereby overcoming the conventional problem of low porosity caused by electrochemical corrosion of large blocks of alloys.
[0097] In the above-described embodiments, the pores are formed by an electrochemical etching process.
[0098] In this embodiment, the pores are formed by electrochemical corrosion, which can improve the efficiency of pore formation. Of course, it is not limited to electrochemical corrosion, and can also be etching.
[0099] In the above embodiment, the porous electrode material is tested for electrocatalytic oxygen production at a current density of 10 mA / cm 2 The overpotential is less than or equal to 285 mV, so that the porous electrode material of the present invention has good conductivity.
[0100] In the above embodiment, a=34.4, b=16.4, c=16.4, d=16.4, and e=16.4.
[0101] In this embodiment, a=34.4, b=16.4, c=16.4, d=16.4, e=16.4, that is, the composition of the porous electrode material is Ni 34.4 Fe 16.4 Co 16.4 Cr 16.4 Al 16.4 By controlling the ratio of five elements, Ni, Fe, Co, Cr and Al, the stability, conductivity and catalytic effect of the porous electrode material in alkaline medium can be maximized.
[0102] In the above embodiments, the crystal structure of the grid-shaped high entropy alloy includes a face-centered cubic lattice and a body-centered cubic lattice.
[0103] In this embodiment, the high entropy alloy of face-centered cubic lattice or body-centered cubic lattice has a higher active area, thereby making the catalytic efficiency higher.
[0104] An embodiment of the second aspect of the present invention provides a method for preparing a porous electrode material.
[0105] Example 1
[0106] See also Figure 1 , this embodiment provides a method for preparing a porous electrode material, comprising the following steps:
[0107] S102: Draw a grid structure model;
[0108] S104: The grid structure model is introduced into a laser 3D metal printing device, and a high entropy alloy powder (composition Ni 34.4 Fe 16.4 Co 16.4 Cr 16.4 Al 16.4 ) to obtain a large block of porous electrode material; wherein the diameter of the focused laser beam is equal to 70 μm, the laser power is equal to 300 W, the laser scanning speed is equal to 1000 mm / s, the laser scanning spacing is equal to 0.05 mm, and the thickness of each printed layer is equal to 20 μm;
[0109] S106: cutting the large block of porous electrode material to obtain small blocks of porous electrode material with a size of 0.8 mm×10 mm×10 mm;
[0110] S108: electrochemically corroding a small block of the porous electrode material using hydrogen chloride and ferrous sulfate corrosive solutions to obtain a porous electrode material; wherein the molar ratio of hydrogen chloride to ferrous sulfate is 2:1, the concentration of hydrogen chloride is 1 mol / L, the concentration of ferrous sulfate is 0.3 mol / L, the current under direct current is 1.5 V, and the power-on time is 1 minute.
[0111] The scanning electron microscope image of the porous electrode material prepared in this example is as follows Fig.10 As shown, the electrochemical performance test of the porous electrode material prepared in this embodiment is carried out, and the specific test steps are as follows:
[0112] The non-electrochemical test part of the porous electrode material prepared in this embodiment was sealed with silicone rubber to expose a fixed area of free surface for electrochemical testing. The electrocatalytic material was tested using a linear voltammetric scanning test method. The test used a three-electrode system, in which the working electrode was the porous electrode material prepared in this embodiment, the reference electrode was mercury / mercuric oxide, the auxiliary electrode was a platinum sheet, and the electrolyte was a 1 mol / L potassium hydroxide solution. The hydrogen evolution polarization curve obtained was as shown in FIG. Figure 7 As shown, Figure 7 It shows that when the current intensity reaches 10mA / cm 2 When , the hydrogen evolution overpotential is 259 mV. This indicates that the porous electrode material in this embodiment has excellent hydrogen evolution catalytic activity.
[0113] Example 2
[0114] See also Figure 2 , this embodiment provides a method for preparing a porous electrode material, comprising the following steps:
[0115] S202: Draw a grid structure model;
[0116] S204: The grid structure model is introduced into a laser 3D metal printing device, and a high entropy alloy powder (composition Ni 34.4 Fe 16.4 Co 16.4 Cr 16.4 Al 16.4 ) to obtain a large block of porous electrode material; wherein the diameter of the focused laser beam is equal to 120 μm, the laser power is equal to 500 W, the laser scanning speed is equal to 1400 mm / s, the laser scanning spacing is equal to 0.15 mm, and the thickness of each printed layer is equal to 40 μm;
[0117] S206: cutting the large block of porous electrode material to obtain small blocks of porous electrode material with a size of 0.8 mm×10 mm×10 mm;
[0118] S208: Electrochemically corroding a small block of the porous electrode material using hydrogen chloride and ferrous sulfate corrosive solutions to obtain a porous electrode material; wherein the molar ratio of hydrogen chloride to ferrous sulfate is 6:1, the concentration of hydrogen chloride is 3 mol / L, the concentration of ferrous sulfate is 0.8 mol / L, the current under direct current is 2 V, and the power-on time is 5 minutes.
[0119] The scanning electron microscope image of the porous electrode material prepared in this example is as follows Fig.11 As shown in the figure, 500 μm is the scale bar. The electrochemical performance test of the porous electrode material prepared in this embodiment is carried out. The specific test steps are as follows:
[0120] The non-electrochemical test part of the porous electrode material prepared in this embodiment was sealed with silicone rubber to expose a fixed area of free surface for electrochemical testing. The electrocatalytic material was tested using a linear voltammetric scanning test method. The test used a three-electrode system, in which the working electrode was the porous electrode material prepared in this embodiment, the reference electrode was mercury / mercuric oxide, the auxiliary electrode was a platinum sheet, and the electrolyte was a 1 mol / L potassium hydroxide solution. The hydrogen evolution polarization curve obtained was as shown in FIG. Figure 8 As shown, Figure 8 It shows that when the current intensity reaches 10 mA / cm2, the hydrogen evolution overpotential is 273 mV, which indicates that the porous electrode material in this embodiment has excellent hydrogen evolution catalytic activity.
[0121] Example 3
[0122] See also Figure 3 , this embodiment provides a method for preparing a porous electrode material, comprising the following steps:
[0123] S302: drawing a grid structure model;
[0124] S304: The grid structure model is introduced into a laser 3D metal printing device, and a high entropy alloy powder (composition Ni 34.4 Fe 16.4 Co 16.4 Cr 16.4 Al 16.4 ) to obtain a large block of porous electrode material; wherein the diameter of the focused laser beam is equal to 90 μm, the laser power is equal to 400 W, the laser scanning speed is equal to 1200 mm / s, the laser scanning spacing is equal to 0.1 mm, and the thickness of each printed layer is equal to 30 μm;
[0125] S306: cutting the large block of porous electrode material to obtain small blocks of porous electrode material with a size of 0.8 mm×10 mm×10 mm;
[0126] S308: Electrochemically corroding a small block of the porous electrode material using hydrogen chloride and ferrous sulfate corrosive solutions to obtain a porous electrode material; wherein the molar ratio of hydrogen chloride to ferrous sulfate is 4:1, the concentration of hydrogen chloride is 2 mol / L, the concentration of ferrous sulfate is 0.5 mol / L, the current under direct current is 1.8 V, and the power-on time is 3 minutes.
[0127] The scanning electron microscope image of the porous electrode material prepared in this example is as follows Fig.12 As shown, the electrochemical performance test of the porous electrode material prepared in this embodiment is carried out, and the specific test steps are as follows:
[0128] The non-electrochemical test part of the porous electrode material prepared in this embodiment was sealed with silicone rubber to expose a fixed area of free surface for electrochemical testing. The electrocatalytic material was tested using a linear voltammetric scanning test method. The test used a three-electrode system, in which the working electrode was the porous electrode material prepared in this embodiment, the reference electrode was mercury / mercuric oxide, the auxiliary electrode was a platinum sheet, and the electrolyte was a 1 mol / L potassium hydroxide solution. The hydrogen evolution polarization curve obtained was as shown in FIG. Fig. 9 As shown, Fig. 9 It shows that when the current intensity reaches 10 mA / cm2, the hydrogen evolution overpotential is 283 mV, which indicates that the porous electrode material in this embodiment has excellent hydrogen evolution catalytic activity.
[0129] Example 4
[0130] See also Figure 4 , this embodiment provides a method for preparing a porous electrode material, comprising the following steps:
[0131] S402: Printing a high entropy alloy powder into a grid-shaped high entropy alloy of a first preset size through a selective laser melting process, wherein the high entropy alloy powder is composed of Ni a Fe b Co c Cr d Al e , 30≤a≤37, 5≤b≤16.7, 5≤c≤16.7, 5≤d≤16.7, 5≤e≤16.7, a+b+c+d+e=100;
[0132] S404: electrochemically corroding the grid-shaped high entropy alloy with a corrosive solution to obtain a porous electrode material;
[0133] The method for preparing a porous electrode material provided by the present invention comprises the following steps: firstly printing a grid-shaped high entropy alloy from high entropy alloy powder by a selective laser melting process; specifically, firstly drawing a grid-shaped molded part data model with pores not less than 200 microns by using CAD drawing software, outputting the file in an STL format, and importing the data model into an SLM device for printing, printing a grid-shaped NiFeCoCrAl high entropy alloy with a pore size of 200 μm to 800 μm at room temperature, wherein the crystal structure is mainly composed of an FCC phase and a BCC phase; and then performing an electrochemical corrosion treatment on the grid-shaped high entropy alloy by using a corrosive liquid to obtain a grid-shaped porous electrode material. The grid-shaped porous electrode prepared by the present invention has pores on the grid-shaped surface, thereby increasing the active area of the electrode material, exposing more catalytic active sites, improving the porosity of the catalyst electrode, and further improving the catalytic effect. It is understandable that the current electrode materials usually subject the entire bulk to electrochemical corrosion treatment, which results in a limited corrosion area and low porosity. The present invention first prepares the high entropy alloy into a grid shape, and then subjecting it to electrochemical corrosion treatment, which greatly increases the contact area with the corrosive liquid, increases the porosity, and thus improves the catalytic effect. In addition, the porous electrode material of the present invention effectively combines the selective laser melting process during the preparation process, thus overcoming the problem of low porosity caused by conventional electrochemical corrosion of large-block alloys.
[0134] In the above embodiment, the mesh size of the mesh-shaped high entropy alloy is greater than or equal to 200 μm and less than or equal to 800 μm.
[0135] In this embodiment, the mesh size of the mesh-like high entropy alloy is limited, which can avoid the mesh size being too small, increasing the difficulty of preparing the mesh, and can also avoid the mesh size being too large, reducing the porosity.
[0136] In the above embodiment, the particle size of the high entropy alloy powder is greater than or equal to 15 μm and less than or equal to 45 μm.
[0137] In this embodiment, controlling the particle size of the high entropy alloy powder can accelerate the melting rate of the high entropy alloy powder and increase the printing rate.
[0138] In the above embodiment, the step of printing a grid-shaped high-entropy alloy of a first preset size from high-entropy alloy powder through a selective laser melting process includes: drawing a grid-shaped structure model; importing the grid-shaped structure model into a laser 3D metal printing device, and printing it through the laser 3D metal printing device to obtain a grid-shaped high-entropy alloy of a first preset size.
[0139] In this embodiment, during the printing process of the high entropy alloy powder, a grid structure model can be drawn first, the grid structure model can be imported into the laser 3D metal printing device, and then printed by the laser 3D metal printing device to obtain a grid-shaped high entropy alloy.
[0140] In the above embodiment, the length of the first preset dimension is greater than or equal to 40 mm and less than or equal to 60 mm; the width of the first preset dimension is greater than or equal to 10 mm and less than or equal to 30 mm; the height of the first preset dimension is greater than or equal to 10 mm and less than or equal to 30 mm.
[0141] In this embodiment, the length of the first preset size is greater than or equal to 40 mm and less than or equal to 60 mm; the width of the first preset size is greater than or equal to 10 mm and less than or equal to 30 mm; the height of the first preset size is greater than or equal to 10 mm and less than or equal to 30 mm. Further, the length, width and height of the first preset size are 50 mm×20 mm×20 mm, that is, during the printing process, the size of the printed grid-shaped high entropy alloy is 50 mm×20 mm×20 mm. Controlling the size of the grid-shaped high entropy alloy can avoid the problem of too small size, resulting in slow printing efficiency, and on the other hand, it can also avoid the problem of too large size resulting in poor corrosion effect in the later stage.
[0142] In the above embodiment, after the step of printing a grid-shaped high entropy alloy of a first preset size from high entropy alloy powder through a selective laser melting process, the step also includes: cutting the grid-shaped high entropy alloy of the first preset size to cut the grid-shaped high entropy alloy to a second preset size.
[0143] In this embodiment, after printing out the grid-shaped high entropy alloy, the grid-shaped high entropy alloy is sawed, which can increase the surface area of the grid-shaped high entropy alloy, and then during the electrochemical corrosion process, the contact area with the corrosion liquid can be increased to improve the pore formation rate.
[0144] In the above embodiment, the length of the second preset dimension is greater than or equal to 0.5 mm and less than or equal to 1 mm; the width of the second preset dimension is greater than or equal to 5 mm and less than or equal to 15 mm; the height of the second preset dimension is greater than or equal to 5 mm and less than or equal to 15 mm.
[0145] In this embodiment, the length of the second preset dimension is greater than or equal to 0.5 mm and less than or equal to 1 mm; the width of the second preset dimension is greater than or equal to 5 mm and less than or equal to 15 mm; the height of the second preset dimension is greater than or equal to 5 mm and less than or equal to 15 mm. Furthermore, the length, width and height of the second preset dimension are 0.8 mm×10 mm×10 mm, that is, the grid-shaped high entropy alloy is cut to a size of 0.8 mm×10 mm×10 mm, which can improve the later pore formation rate.
[0146] In the above embodiment, the etching solution includes an acid solution and ferrous sulfate.
[0147] In this embodiment, a mixture of hydrogen chloride and ferrous sulfate is selected as the etching solution, which has a better etching effect than a mixture of hydrogen chloride and chromium trioxide, and can make the porous electrode material have better alkali resistance and stability.
[0148] In the above embodiments, the acid solution includes hydrogen chloride.
[0149] In the above embodiment, the molar ratio of hydrogen chloride to ferrous sulfate is greater than or equal to 2:1 and less than or equal to 6:1.
[0150] In this embodiment, the molar ratio of hydrogen chloride to ferrous sulfate is controlled to maximize the corrosion effect and improve the alkali resistance stability.
[0151] In the above embodiment, the concentration of hydrogen chloride is greater than or equal to 1 mol / L and less than or equal to 3 mol / L.
[0152] In this embodiment, controlling the concentration of hydrogen chloride can ensure the optimal pH value of the etching solution. Too high a concentration will result in an excessively high pH value of the etching solution, which is not conducive to pore formation and will affect the alkali resistance stability of the porous electrode material.
[0153] In the above embodiment, the concentration of ferrous sulfate is greater than or equal to 0.3 mol / L and less than or equal to 0.8 mol / L.
[0154] In this embodiment, the concentration of ferrous sulfate is greater than or equal to 0.3 mol / L and less than or equal to 0.8 mol / L, for example, 0.5 mol / L, which can ensure the pore-forming effect and avoid the problem of excessive ferrous sulfate and insignificant improvement in pore effect, resulting in waste of materials.
[0155] In the above embodiment, in the step of electrochemical corrosion treatment, the electrochemical corrosion treatment conditions include: direct current, the power-on current is greater than or equal to 1.5V and less than or equal to 2V, and the power-on time is greater than or equal to 1 minute and less than or equal to 5 minutes.
[0156] In this embodiment, electrochemical corrosion is performed by direct current. Furthermore, the current is greater than or equal to 1.5V and less than or equal to 2V, for example, the current is 1.8V, and the power-on time is greater than or equal to 1 minute and less than or equal to 5 minutes, for example, 3 minutes. By controlling the current and the power-on time, the pore-making effect can be improved while improving the utilization rate of energy and avoiding energy waste.
[0157] In the above embodiment, during the printing process, the printing environment of the laser 3D metal printing device is an argon environment.
[0158] In this embodiment, the printing environment of the laser 3D metal printing device is an argon environment, preferably high-purity argon, which can ensure a safe printing environment.
[0159] In the above embodiment, during the printing process, the diameter of the focused laser beam of the laser 3D metal printing device is greater than or equal to 70 μm and less than or equal to 120 μm.
[0160] In this embodiment, the diameter of the focused laser beam of the laser 3D metal printing device is greater than or equal to 70 μm and less than or equal to 120 μm. Further, the diameter of the focused laser beam of the laser 3D metal printing device is 90 μm, which can ensure the printing speed and the accuracy of the pores, thereby improving the catalytic effect of the porous electrode material.
[0161] In the above embodiment, the laser power of the laser 3D metal printing device is greater than or equal to 300W and less than or equal to 500W.
[0162] In this embodiment, the laser power of the laser 3D metal printing device is greater than or equal to 300 W and less than or equal to 500 W. Furthermore, the laser power of the laser 3D metal printing device is 400 W. By controlling the laser power of the laser 3D metal printing device, the printing speed can be guaranteed, the accuracy of the pores can be ensured, and the catalytic effect of the porous electrode material can be improved.
[0163] In the above embodiment, during the printing process, the scanning speed of the laser of the laser 3D metal printing device is greater than or equal to 1000 mm / s and less than or equal to 1400 mm / s.
[0164] In this embodiment, during the printing process, the scanning speed of the laser of the laser 3D metal printing device is greater than or equal to 1000 mm / s and less than or equal to 1400 mm / s. Further, the scanning speed of the laser of the laser 3D metal printing device is 1200 mm / s. By controlling the scanning speed of the laser of the laser 3D metal printing device, the printing rate can be guaranteed on the one hand, and the quality of the porous electrode material can be guaranteed on the other hand, so as to avoid the catalytic effect of the porous electrode material being affected by the printing speed being too fast.
[0165] In the above embodiment, the scanning pitch of the laser of the laser 3D metal printing device is greater than or equal to 0.05 mm and less than or equal to 0.15 mm.
[0166] In this embodiment, the scanning pitch of the laser of the laser 3D metal printing device is greater than or equal to 0.05 mm and less than or equal to 0.15 mm. Further, the scanning pitch of the laser of the laser 3D metal printing device is equal to 0.09 mm. Controlling the scanning pitch of the laser of the laser 3D metal printing device can ensure the quality of the porous electrode material and improve the catalytic effect.
[0167] In the above embodiment, the thickness of each layer printed by the laser 3D metal printing device is greater than or equal to 20 μm and less than or equal to 40 μm.
[0168] In this embodiment, the thickness of each layer printed by the laser 3D metal printing device is greater than or equal to 20 μm and less than or equal to 40 μm. Further, the thickness of each layer printed by the laser 3D metal printing device is 30 μm. Controlling the thickness of each layer printed by the laser 3D metal printing device can ensure the quality of the porous electrode material and improve the catalytic effect.
[0169] Comparative Example 1
[0170] See also Figure 5 This comparative example provides a method for preparing an electrode material, comprising the following steps:
[0171] S502: drawing a grid structure model;
[0172] S504: The grid structure model is introduced into a laser 3D metal printing device, and a high entropy alloy powder (composition Ni 34.4 Fe 16.4 Co 16.4 Cr 16.4 Al 16.4 ) to obtain a large block of porous electrode material; wherein the diameter of the focused laser beam is equal to 90 μm, the laser power is equal to 400 W, the laser scanning speed is equal to 1200 mm / s, the laser scanning spacing is equal to 0.1 mm, and the thickness of each printed layer is equal to 30 μm;
[0173] S506: Cut the large block of the porous electrode material to obtain small blocks of the porous electrode material of 0.8 mm×10 mm×10 mm as the porous electrode material.
[0174] The electrochemical performance of the porous electrode material prepared in this comparative example was tested. The specific test steps were the same as those of each of the above examples. The results showed that when the current intensity reached 10 mA / cm 2 When the hydrogen evolution overpotential is 353 mV, it indicates that the porous electrode material in this comparative example has poor hydrogen evolution catalytic activity. This is because it is not corroded by the corrosive liquid, so that a large number of pores are not generated on the surface of the prepared electrode material, which makes the conductivity low.
[0175] Comparative Example 2
[0176] See also Figure 6 This comparative example provides a method for preparing a porous electrode material, comprising the following steps:
[0177] S602: The bulk of the high entropy alloy obtained in S504 in Comparative Example 1 is subjected to electrochemical corrosion treatment by means of hydrogen chloride and ferrous sulfate corrosion solutions to obtain a porous electrode material; wherein the molar ratio of hydrogen chloride to ferrous sulfate is equal to 4:1, the concentration of hydrogen chloride is equal to 2 mol / L, the concentration of ferrous sulfate is equal to 0.5 mol / L, the current under direct current is equal to 1.8 V, and the power-on time is equal to 3 minutes.
[0178] The electrochemical performance of the porous electrode material prepared in this comparative example was tested. The specific test steps were the same as those of each of the above examples. The results showed that when the current intensity reached 10 mA / cm 2 When , the hydrogen evolution overpotential is 360 mV, which indicates that the porous electrode material in this comparative example has poor hydrogen evolution catalytic activity. This is because although the large block of the high entropy alloy is corroded by the corrosive liquid, the contact area between the high entropy alloy and the corrosive liquid is small during the corrosion process, which makes the prepared porous electrode material have a low porosity, and thus makes the active area of the electrode material smaller, the active sites are fewer, and the conductivity is lower.
[0179] An embodiment of the third aspect of the present invention provides an application of a porous electrode material in the electrolysis of water to produce hydrogen and / or oxygen. The porous electrode material used is a porous electrode material according to any embodiment of the first aspect of the present invention or a porous electrode material prepared by the method for preparing a porous electrode material according to any embodiment of the second aspect of the present invention.
[0180] An embodiment of the fourth aspect of the present invention provides a catalyst electrode 12, which is prepared by a porous electrode material according to any embodiment of the first aspect of the present invention, or a porous electrode material prepared by a preparation method of a porous electrode material according to any embodiment of the second aspect of the present invention.
[0181] See also Fig.13 The embodiment of the fifth aspect of the present invention provides an electrolysis device 1, comprising a catalyst electrode 12 according to the embodiment of the fourth aspect of the present invention.
[0182] Beneficial effect: The porous electrode material provided by the present invention has excellent water electrolysis oxygen production activity and stability in alkaline medium. -2 The required overpotential is 270mV to 280mV and can be applied at 500mA·cm -2 It can work continuously for 1000 hours under high temperature and its performance is better than that of nickel foam.
[0183] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features claimed herein.
Claims
1. A porous electrode material, characterized in that: The invention comprises a grid-shaped high entropy alloy, wherein the composition of the grid-shaped high entropy alloy is Ni a Fe b Co c Cr d Al e , 30≤a≤37, 5≤b≤16.7, 5≤c≤16.7, 5≤d≤16.7, 5≤e≤16.7, a+b+c+d+e=100, and the grid-like high-entropy alloy surface has pores.
2. The porous electrode material according to claim 1, characterized in that The pores have a pore diameter greater than or equal to 150 μm and less than or equal to 1000 μm.
3. The porous electrode material according to claim 1, characterized in that: The mesh size of the mesh-shaped high entropy alloy is greater than or equal to 200 μm and less than or equal to 800 μm; and / or The grid-shaped high entropy alloy is formed by printing through a selective laser melting process; and / or The pores are formed by an electrochemical etching process; and / or The porous electrode material has a current density of 10 mA / cm in the electrocatalytic oxygen production test. 2 The overpotential is less than or equal to 285mV.
4. The porous electrode material according to claim 1, characterized in that a=34.4, b=16.4, c=16.4, d=16.4, and e=16.
4.
5. The porous electrode material according to claim 1, characterized in that: The crystal structure of the grid-shaped high entropy alloy includes a face-centered cubic lattice and a body-centered cubic lattice.
6. A method for preparing a porous electrode material, characterized in that: The steps include: A high entropy alloy powder is printed into a grid-shaped high entropy alloy of a first preset size by a selective laser melting process, wherein the composition of the high entropy alloy powder is Ni a Fe b Co c Cr d Al e , 30≤a≤37, 5≤b≤16.7, 5≤c≤16.7, 5≤d≤16.7, 5≤e≤16.7, a+b+c+d+e=100; The grid-shaped high entropy alloy is subjected to electrochemical corrosion treatment by using a corrosive solution to obtain the porous electrode material.
7. The method for preparing a porous electrode material according to claim 6, characterized in that: The particle size of the high entropy alloy powder is greater than or equal to 15 μm and less than or equal to 45 μm.
8. The method for preparing a porous electrode material according to claim 6, characterized in that: The step of printing a grid-shaped high entropy alloy of a first preset size from high entropy alloy powder by a selective laser melting process comprises: Draw a grid-like structure model; The grid structure model is introduced into a laser 3D metal printing device, and is printed by the laser 3D metal printing device to obtain a grid-shaped high-entropy alloy of the first preset size.
9. The method for preparing a porous electrode material according to claim 8, characterized in that: The length of the first preset size is greater than or equal to 40 mm and less than or equal to 60 mm; The width of the first preset size is greater than or equal to 10 mm and less than or equal to 30 mm; The height of the first preset dimension is greater than or equal to 10 mm and less than or equal to 30 mm.
10. The method for preparing a porous electrode material according to claim 6, characterized in that: After the step of printing the high entropy alloy powder into a grid-shaped high entropy alloy of a first preset size by the selective laser melting process, the method further includes: The first preset size grid-shaped high entropy alloy is cut to cut the grid-shaped high entropy alloy to a second preset size.
11. The method for preparing a porous electrode material according to claim 10, characterized in that: The length of the second preset size is greater than or equal to 0.5 mm and less than or equal to 1 mm; The width of the second preset size is greater than or equal to 5 mm and less than or equal to 15 mm; The height of the second preset size is greater than or equal to 5 mm and less than or equal to 15 mm.
12. The method for preparing a porous electrode material according to claim 11, characterized in that: The length, width and height of the second preset size are 0.8 mm×10 mm×10 mm.
13. The method for preparing a porous electrode material according to claim 6, characterized in that: The etching solution includes an acid solution and ferrous sulfate.
14. The method for preparing a porous electrode material according to claim 13, characterized in that: The acid solution includes hydrogen chloride.
15. The method for preparing a porous electrode material according to claim 14, characterized in that: The molar ratio of the hydrogen chloride to the ferrous sulfate is greater than or equal to 2:1 and less than or equal to 6:1; The concentration of the hydrogen chloride is greater than or equal to 1 mol / L and less than or equal to 3 mol / L; and / or The concentration of the ferrous sulfate is greater than or equal to 0.3 mol / L and less than or equal to 0.8 mol / L.
16. The method for preparing a porous electrode material according to claim 6, characterized in that: In the step of electrochemical corrosion treatment, the electrochemical corrosion treatment conditions include: direct current, power-on current greater than or equal to 1.5V and less than or equal to 2V, and power-on time greater than or equal to 1 minute and less than or equal to 5 minutes.
17. The method for preparing a porous electrode material according to claim 8, characterized in that: In the step of printing by the laser 3D metal printing device, the printing environment of the laser 3D metal printing device is an argon gas environment; In the step of printing by the laser 3D metal printing device, the diameter of the focused laser beam of the laser 3D metal printing device is greater than or equal to 70 μm and less than or equal to 120 μm; and / or In the step of printing by the laser 3D metal printing device, the laser power of the laser 3D metal printing device is greater than or equal to 300W and less than or equal to 500W; and / or In the step of printing by the laser 3D metal printing device, the scanning speed of the laser of the laser 3D metal printing device is greater than or equal to 1000 mm / s and less than or equal to 1400 mm / s; and / or In the step of printing by the laser 3D metal printing device, the scanning pitch of the laser of the laser 3D metal printing device is greater than or equal to 0.05 mm and less than or equal to 0.15 mm; and / or In the step of printing by the laser 3D metal printing device, the thickness of each layer printed by the laser 3D metal printing device is greater than or equal to 20 μm and less than or equal to 40 μm; and / or In the step of printing by the laser 3D metal printing device, the diameter of the focused laser beam of the laser 3D metal printing device is 90 μm; and / or In the step of printing by the laser 3D metal printing device, the laser power of the laser 3D metal printing device is 400W; and / or In the step of printing by the laser 3D metal printing device, the scanning speed of the laser of the laser 3D metal printing device is 1200 mm / s; and / or In the step of printing by the laser 3D metal printing device, the scanning pitch of the laser of the laser 3D metal printing device is equal to 0.09 mm; In the step of printing by the laser 3D metal printing device, the thickness of each layer printed by the laser 3D metal printing device is 30 μm.
18. Use of the porous electrode material according to any one of claims 1 to 5 or the method for preparing the porous electrode material according to any one of claims 6 to 17 in electrolyzing water to produce hydrogen and / or oxygen.
19. A catalyst electrode, characterized in that: The catalyst electrode is prepared from a porous electrode material according to any one of claims 1 to 5 or a porous electrode material prepared by the method for preparing a porous electrode material according to any one of claims 6 to 17.
20. An electrolysis device, characterized in that: include The catalyst electrode as claimed in claim 19.
Citation Information
Patent Citations
Micro-nano porous functional device and additive manufacturing method and application thereof
CN113290242A
Preparation method and application of multilevel structure high-entropy alloy material for catalytic electrode
CN114799206A
High-activity micro-nano porous high-entropy alloy full-electrolysis water catalytic material and preparation thereof
CN115198299A
Method and apparatus for video encoding / decoding using intra block copy
KR1020200108798A